EFFECT OF AVA, MVA, CFVA ON STOCK PRICE PT. WIJAYA KARYA (PERSERO) YEAR 2006-2020 - Widuhung, Sisca Debyola; Aris Machmud (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Total management performance is assessed based on the increase in the welfare ofmultiple stakeholders (investors, customers, and employees) – and especially theachievement of SVA (Shareholders Value Added), to create wealth for investors orbusiness owners. This study aims to determine the stock price of PT. Wijaya Karya(Persero) Tbk. which is influenced by EVA, MVA and CFVA the method used is aresearch based on statistical analysis techniques using regression and correlation andtesting the hypothesis based on a time series approach, the results of this study areBased on the results of the calculations in table above, it can be concluded that thevalue of the Adjusted R-Squared is 0.784382 or 78.44%, meaning that the independentvariables (Economic Value Added and Free Cash Flow) can explain the dependentvariable (Stock Price) of 78.44% and then 21.56 % is explained by other variablesoutside of this study